Global status of research on cutaneous squamous cell carcinoma and its programmed cell death: Bibliometric and visual analysis from 2012 to middle 2022 - Zhang, Yalin; Guo, Zhigang; Wang, Huimin; Li, Bo (Frontiers in Oncology, 2023)
Objective This study was aimed to analyze the research status and development trend of cutaneous squamous cell carcinoma (CSCC), focusing on the field of programmed cell death of CSCC, and providing suggestions for the research of CSCC. Methods The publications related to CSCC and CSCC programmed cell death were searched in the Web of Science Core Collection (WOSCC) database, and timespan was set from 2012 to middle 2022. Research trends, authors, major country collaborations, research institutions, representative journals, publishers, and keywords were analyzed with CiteSpace and VOSviewer. Results After screening, a total of 3656 publications on CSCC and 156 publications on CSCC cell programmed death were obtained. The number of published articles increased gradually with the years. The United States ranked first in terms of the number of published papers. Research in this field had focused on dermatology. Most of the institutions in both regions were from European and American countries. Harvard University was the most prolific institution. Wiley was the most prolific publisher. The popular keywords for programmed cell death in CSCC were cutaneous squamous cell carcinoma, diagnosis, pd 1, head, nivolumab and risk. Keywords in CSCC field were divided into 7 clusters: cutaneous squamous cell carcinoma, sentinel lymph node biopsy, skin cancer, B-Raf Proto-Oncogene, Serine/Threonine Kinase (BRAF) inhibitor and human Papillomaviruses, and P63 expression. Squamous cell carcinoma, cancer, head and expression were the most popular keywords. The popular keywords for programmed cell death in CSCC were cutaneous squamous cell carcinoma, diagnosis, pd 1, head, nivolumab and risk. Conclusion This study analyzed the research status of cutaneous squamous cell carcinoma and programmed cell death from 2012 to middle 2022. Understanding research status and hotspots can help scholars, countries and policymakers to better understand the background and research frontier of CSCC, and guide further research directions.